Death inducing and cytoprotective autophagy in T‐47D cells by two common antibacterial drugs: sulphathiazole and sulphacetamide. (1st March 2013) - Mohammadpour, Raziye; Safarian, Shahrokh; Sheibani, Nader; Norouzi, Saeed; Razazan, Atefeh
Abstract The broad spectrum of the pharmacological effects of sulphonamide family of drugs motivated us to investigate the cellular mechanisms for anti‐cancer effects of sulphathiazole and sulphacetamide on T‐47D breast cancer cells. Fluorescent microscopy, flow cytometric analysis, caspase‐3 activity and DNA fragmentation assays were used to detect apoptosis. The distribution of the cells among different phases of the cell cycle was measured by flow cytometry. The expression of several genes with important roles in some critical cellular pathways including apoptosis, mTOR/AKT pathway and autophagy were determined by real‐time RT‐PCR analysis. Sulphathiazole and sulphacetamide induced anti‐proliferative effects on T‐47D cells were independent of apoptosis and cell cycle arrest. The overexpression of critical genes involved in autophagy including ATG5, p53 and DRAM indicated that the main effect of the drug‐induced anti‐proliferative effects was through induction of autophagy. This process was induced in two different forms, including death inducing and cytoprotective autophagy. Sulphathiazole treatment was followed by higher expression of p53/DRAM and downregulation of Akt/mTOR pathway resulting in death autophagy. In contrast, sulphacetamide treatment lowered expression of p53/DRAM pathway in parallel with upregulation of Akt/mTOR pathway promoting cytoprotective autophagy. The results indicated that autophagy is the main mechanism mediating the anti‐cancer effects of sulphathiazole and sulphacetamide on T‐47D cells. Alignment of the p53 and DRAM expression along with activation level of Akt survival pathway therefore determines the type of autophagy that occurs.